The Role of Metaphorical Thinking in the Creativity of Scientific Discourse - Sanchez-Ruiz, Maria-José (2013)
This article critically reviews the extant literature on scientific creativity and metaphorical thinking. Metaphorical thinking is based on a conceptual transfer of relationships or mapping, from a well-known source domain to a poorly known target domain, which could result in creative outcomes in sciences. Creativity leads to products that are deemed to be novel and original as well as useful and adaptive. After reviewing the concepts of metaphor and analogy and the types of metaphor identified in the literature, the relationships traditionally theorized between metaphors and creativity from different scientific disciplines were discussed, with special focus on the psychology of creativity. The empirical study of the links between creativity and metaphors can contribute to a better understanding of the scientific process. Promising lines for future research are advanced, such as the exploration of the relationship between the presence of certain types of metaphors in scientific theories and the level of creativity of such theories.